INSTAGRAM AS A TEACHING TOOL? REALLY? - Fitri Handayani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The use of social media becomes more popular for the students nowadays. Social media is web-based application that allows users to communicate, collaborate, and share resources with other people. Both being easy to access and easy to use make social media become a very effective tool to communicate and exchange ideas. Students may use social media to keep up with their friends, to stay up-to-date with news and current events, to fill up spare time, to find entertaining content, and to share opinions. Thus, the popularity of the social media among students can be used as a tool in language teaching. One of the popular social media is Instagram. It is a social network that enables its users to take pictures and videos, and share them publicly or privately on the application, as well as through a variety of other social network, such as Facebook and Twitter. Through Instagram the students can post photos or videos that can be commented by their followers. By using Instagram teachers are offered greatopportunity to develop classroom activities creatively. This paper will give an overview of the main advantages of using Instagram for EFL and offer a list of activities for which Instagram can be used.